Guidelines to the cost-benefit analysis and the proceedings from a CARICOM course held in Barbados on cost-benefit analysis for the CSME - Watson, Noel ([CCS] [Georgetown]GY, 1996)
Focuses on the range of variables/factors to be affected by the CSME. Looks at the costs and benefits to individual countries, to other Regional countries and the Region as a whole. Deals with the tools of cost-benefit analysis.